Pelatihan Dasar IoT Menggunakan ESP32 Bagi Siswa SMK NU Tasikmalaya - Dinata, Ilham; Fajar Firmansyah; Indra Setiawan (Jurnal Teknologi Informasi untuk Masyarakat, 2025)
The development of Internet of Things (IoT) technology is increasingly rapid and has been widely applied in various fields ranging from industry, health, agriculture to education. However, the understanding of vocational middle level students regarding IoT concepts and implementations is still limited, especially in the application of simple hardware such as ESP32. This condition is a challenge as well as an opportunity to provide basic IoT introduction and training so that students can improve their technological competence according to the needs of the digital era. This Community Service (PkM) activity aims to provide a basic understanding of the concept of IoT and train SMK NU Tasikmalaya students in using the ESP32 Microcontroller for simple projects. Through this training, it is hoped that students will be able to get to know IoT hardware, understand data communication flows and be able to build basic applications such as real-time sensor monitoring. The method of implementing PkM is carried out through a short workshop approach consisting of delivering basic IoT concept materials, introduction to ESP32 devices and direct practice of making simple IoT projects. This training is carried out with demonstration methods and independent practice so that students can more easily understand and be able to apply the knowledge obtained. This activity is expected to improve students' digital literacy and basic skills in the field of IoT so that it can be a provision to develop competencies in the world of work and continue higher education.